2005
DOI: 10.1113/jphysiol.2005.087643
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for parasympathetic vasodilator fibres in the rat masseter muscle

Abstract: The present study was designed to examine (1) whether there are vasodilator fibres in the masseter muscle, and (2) if there are, to establish the neural pathways mediating these responses in urethane-anaesthetized rats. Electrical stimulation of the central cut end of the lingual nerve (LN) elicited intensity-and frequency-dependent increases of the blood flow in the masseter muscle (MBF) and lower lip (LBF). Increases in both the MBF and LBF evoked by the LN stimulation were reduced by hexamethonium in a dose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…These observations suggest that the evoked MBF increases as a result of "vasodilation." Although blood vessels in the masseter muscle are innervated with sympathetic postganglionic neurons derived from the superior cervical ganglion, these neurons did not contribute to the observed MBF increases evoked by cVN stimulation, since bilateral sectioning of the CST in the present study cuts the preganglionic inputs to the superior cervical ganglion, which projects postganglionic fibers to the cranial circulation (see MATERIALS AND METHODS), and electrical stimulation of the CST consistently reduced MBF, as reported by our previous reports (14,15). Therefore, we hypothesize that the cVN stimulationinduced vasodilation in the masseter muscle is mediated by a mechanism involving a parasympathetic reflex.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…These observations suggest that the evoked MBF increases as a result of "vasodilation." Although blood vessels in the masseter muscle are innervated with sympathetic postganglionic neurons derived from the superior cervical ganglion, these neurons did not contribute to the observed MBF increases evoked by cVN stimulation, since bilateral sectioning of the CST in the present study cuts the preganglionic inputs to the superior cervical ganglion, which projects postganglionic fibers to the cranial circulation (see MATERIALS AND METHODS), and electrical stimulation of the CST consistently reduced MBF, as reported by our previous reports (14,15). Therefore, we hypothesize that the cVN stimulationinduced vasodilation in the masseter muscle is mediated by a mechanism involving a parasympathetic reflex.…”
Section: Discussionsupporting
confidence: 66%
“…Anesthetized animals were intubated, paralyzed by intravenous injection of pancuronium bromide (Mioblock; Organon, Teknika, The Netherlands; 0.6 mg/kg initially, supplemented with 0.4 mg/kg every hour or so after testing the level of anesthesia; see below), and artificially ventilated with a mixture of 50% air-50% O2 via a tracheal cannula. A ventilator (model SN-480 -7; Shinano, Tokyo, Japan) was set to deliver a tidal volume of 8.5-10 cm 3 /kg at a rate of 20 -23 breaths/min, and the end-tidal concentration of CO2 was determined by means of an infrared analyzer (Capnomac Ultima; Datex, Helsinki, Finland), as reported elsewhere (14). Rectal temperature was maintained at 37-38°C with the use of a heating pad.…”
Section: Preparation Of Animalsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Gourine et al reported that RIPC might be associated with the nerve reflex, which is the sensory afferent pathway from the peripheral organ (limbs) and parasympathetic vagal efferent outflow to the heart in rats [20]. Previous studies showed that there is evidence of parasympathetic vasodilator in the masseter muscle [21], lower lip [22] and brain vessels [23] in animals. Those findings indicated that vasodilatation is a result of reflex via increasing parasympathetic activity.…”
Section: Discussionmentioning
confidence: 98%
“…Rats were intubated, paralyzed by an intravenous injection of pancuronium bromide (Mioblock; Organon Teknika, Netherlands; 0.6 mg/kg initially, supplemented with 0.4 mg/kg every hour), and artificially ventilated with a 50:50 mixture of air and O 2 via a tracheal cannula. The ventilator (model SN-480-7; Shinano, Tokyo, Japan) was set with a tidal volume of 5.0 -7.5 cm 3 /kg at a rate of 18 -20 breaths/min, and the end-tidal concentration of CO 2 was determined by an infrared analyzer (Capnomac Ultima; Datex, Helsinki, Finland), as previously described (7). Rectal temperature was maintained at 37°C with a heating pad.…”
Section: Methodsmentioning
confidence: 99%